"Don't smoke in public, you look like trash": An exploratory study about women's experiences of smoking-related stigmatisation and the connection to neighbourhood-level deprivation. (July 2019) - McCready, Geneviève; Glenn, Nicole M.; Frohlich, Katherine L.
Abstract: In this exploratory qualitative study we used Goffman's theory of stigmatisation to examine how women experience smoking-related stigma in relation to neighbourhood-level deprivation. From an existing cohort, we recruited fifteen women who smoked. We found differences in the women's experiences and abilities to negotiate and avoid a stigmatised smoking identity based on neighbourhood-level deprivation. Women in high-deprivation neighbourhoods described limited access to such places and this restricted their abilities to 'pass' as non- or not-quite-smokers and avoid smoking-related stigmatisation. We discuss the implications of the findings in relation to social-spatial inequalities in health and public health policy. Highlights: Smoking-related stigma can add to existing social inequalities. Opportunities for 'passing' are unevenly distributed across neighbourhoods. Women in low-deprivation neighbourhoods were able to bypass stigma more easily. Women in high-deprivation neighbourhoods reported added stigma (spatial, gendered). More attention should be paid to unintended consequences of tobacco denormalization.